Semiotic Analysis of Profit Sharing in Islamic Finance: A Critical Study of Roland Barthes - Cahya, Bayu Tri; Azliani, Firda Nur; Mohd Ali, Nor Aishah; Saputri, Dilla Ajeng Diah; Marpaung, Muslim (Share: Jurnal Ekonomi dan Keuangan Islam, 2025)
Within the context of Islamic finance, profit sharing represents more than a mere economic mechanism, yet its deeper symbolic meanings remain underexplored. This study aims to uncover the layered meanings of profit sharing through denotation, connotation, and myth using Roland Barthes's semiotic framework. Employing a qualitative approach with a postmodernist perspective, data were collected through field research involving in-depth interviews with nine informants, supplemented by secondary literature reviews. The findings reveal that profit sharing operates on three semiotic levels: denotatively as cooperation and mutual agreement; connotatively as mutual assistance, responsibility, and rejection of injustice reflecting the Prophet Muhammad SAW's example; and mythologically as connected to the traditional "paron" system and interpreted as employee financing or empowerment. These findings demonstrate that profit sharing transcends economic transactions to function as a cultural and symbolic system embodying justice, collective welfare, and moral values, often illustrated through metaphors of bees and voluntary cooperation, thereby positioning it as both a financial instrument and a vehicle for social equity within Islamic economic principles. Abstrak Analisis Semiotik Bagi Hasil dalam Keuangan Islam: Studi Kritis Roland Barthes. Dalam konteks keuangan Islam, bagi hasil tidak hanya merepresentasikan mekanisme ekonomi, namun juga makna simbolik mendalam yang belum tereksplorasi secara memadai. Penelitian ini bertujuan untuk mengungkap makna-makna tersembunyi di balik konsep dan praktik bagi hasil dalam konteks keuangan Islam, melalui pendekatan semiotika Roland Barthes. Dengan menggunakan pendekatan kualitatif berperspektif postmodernis, data dikumpulkan melalui penelitian lapangan yang melibatkan wawancara mendalam dengan sembilan informan, dilengkapi dengan tinjauan literatur sekunder. Temuan menunjukkan bahwa bagi hasil beroperasi pada tiga tingkat semiotik: secara denotatif sebagai kerja sama dan kesepakatan bersama; secara konotatif sebagai bantuan timbal balik, tanggung jawab, dan penolakan terhadap ketidakadilan yang mencerminkan teladan Nabi Muhammad SAW; dan secara mitologis sebagai yang terhubung dengan sistem tradisional "paron" dan diinterpretasikan sebagai pembiayaan atau pemberdayaan karyawan. Temuan ini menunjukkan bahwa bagi hasil melampaui transaksi ekonomi untuk berfungsi sebagai sistem budaya dan simbolik yang mewujudkan keadilan, kesejahteraan kolektif, dan nilai-nilai moral, sering digambarkan melalui metafora lebah dan kerja sama sukarela, sehingga memposisikannya baik sebagai instrumen keuangan maupun wahana untuk kesetaraan sosial dalam prinsip ekonomi Islam.